Electrochemical Determination of Uric Acid, Dopamine and Tryptophan at Zinc Hexacyanoferrate Clay Modified Electrode. Issue 10 (18th June 2015) - Kemmegne‐Mbouguen, Justin Claude; Angnes, Lúcio; Mouafo‐Tchinda, Edwige; Ngameni, Emmanuel
Abstract A Cameroonian smectite clay has been transformed into Zn2+ homoionic form and then used to prepare film modified glassy carbon electrodes and carbon paste electrodes. These electrodes containing Zn2+ were exploited to prepare a mixed valence zinc hexacyanoferrate (ZnHCF). Cyclic voltammetry has been employed to monitor the in situ growth of ZnHCF on clay modified electrodes. Although interesting electrocatalytic properties toward UA were observed with these modified electrodes, the modified carbon paste electrodes were the most suitable for dopamine, uric acid and tryptophan detection and exhibited for these analytes extended linear range, high sensitivities, selectivity and low limit.